Leadership development for missions in poor urban communities - Kabongo, Kasebwe T. L. (HTS teologiese studies, 2019)
Leadership development is an ongoing need in Africa. Good leadership is key to the building of any society. This article is written from the perspective of someone who lives in an African community of poverty. As he or she observes the many problems the African continent faces, he or she wonders about the role of the church to participate in seeking solutions to these problems. The article stresses that effective leadership development should equip people to be participants of the flourishing of their communities. It discusses the theological and missiological foundations of leadership as avenues to align leadership formation with the improvement of the quality of life of Africans living in communities of poverty. The researcher belongs to a missional community which focuses on discipling local residents, with the hope of nurturing agency from inside out. He uses the autoethnographic methodology to describe this case study of his missional community efforts.